Estudo da previsibilidade de tonalidades na decoração em vidrados transparentes - Gibertoni, Claudia (Universidade Federal de São Carlos, 2008)
This study aimed to streamline the use and provide for the tone in the implementation of the decoration in glazed. The industry of traditional ceramics uses a range of dyes and pigments for the decoration of products. Often, it has sought empirical way of reducing the number of pigments, creating a palette of colors optimized to meet the needs of decorative glazed ceramic, reproducing the largest possible number of shades. The main objective of this work was the development of a methodology to provide a certain tone, even during the stage of the project decorative graphics in place to empiricism, until now very common in the industry of tiles. The work involved, initially, experiments with formulations combining dyes, basic glass and vehicle. A series of dyes, dosing methods, industrial paints, reproduced paints in laboratory and commercial products, as well graphic print were evaluated. The dyes were physico-chemical characterized and in addiction the resulting glazes were characterized by the colour of reflectance with spectrophotometer, creating a database of chromatic coordinates (L*, a* and b*). Different colour models, such as RGB (digital image), CMYK (graphic print) and CIE- L*a*b* (ceramic sample) were compared. Based on the database and Kubelka-Munk Theory, a series of calculation were made to adjust the product tonalities to the foreseen tonalities and the captured image. The results showed that some colours presented higher deviation than those obtained in the case of the monitor, paper and sample, specially the black and green. No linear behavior was observed with the addition of the dyes. The evaluation of the dosing method of the dyes (weight percent or volume percent), showed no difference between them. The calculation for the foreseen tonalities showed that the Kubelka-Munk Theory is difficult to be applied for transparent and semi-transparent glazes.
Use of pigments and previsibility of tonalities in the decoration of ceramic glazes
Keywords: Cerâmica; Revestimentos cerâmicos; Decoração; Variação de tonalidade; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA